The Association between Atopy, and Family History of Asthma Patient and Severity Asthma based on Spirometry - Susanthy Djajalaksana; Aditya Sri Listyoko; M. Yusuf Musthafa; Didik Purbandiyono; Adrian Yusdianto; Adlan Pratama Binharyanto; Cindy Carrissa Primaputri; Ilham Revan Ananda; Marsha Nurandhini; Muli Yaman; Reza Aditya Mahendra; Zata Dini (Medica Hospitalia : Journal of Clinical Medicine, 2025)
BACKGROUND: Asthma is a chronic inflammatory respiratory condition characterized by fluctuating symptoms, which often leads to diagnostic challenges. Accurate assessment and interpretation of clinical and functional parameters are essential to improve disease management and patient outcomes. AIMS: This study aims to analyze the demographic and clinical profiles of asthma patients, particularly investigating the relationships among the degree of airway obstruction, spirometric indices, smoking exposure, environmental risk factors, atopic history, and family history, to better understand the multifactorial nature of asthma. METHOD: A retrospective descriptive-analytic study was conducted using medical records of 107 asthma patients treated at the Outpatient Installation of the Lung Polyclinic, Wlingi General Hospital, Blitar Regency, from 2021 to 2022. Descriptive statistics were used to summarize demographic and clinical data, and Spearman correlation tests assessed associations between variables. RESULTS: A high proportion of patients had a history of smoking, with 22.4% being active and 52.3% passive smokers. However, no significant correlation was found between smoking status and asthma control. Common environmental risk factors included exposure to dust and cold air, though these did not consistently correlate with asthma exacerbations. Significant correlations were identified between the severity of airway obstruction and spirometric parameters such as FEV1, FVC, FEV1/FVC ratio, PEF, FEF 25, FEF 50, and FEF 75, confirming the impact of airflow limitation on lung function. No significant associations were found between asthma stability and atopic or family history. CONCLUSION: The findings underscore the complexity of asthma pathophysiology, where airflow obstruction is clearly linked to reduced spirometric function, but other factors such as smoking, environmental exposures, atopy, and family history do not show consistent predictive value for asthma control. These results highlight the need for a comprehensive and individualized approach in asthma diagnosis and management.